Cd(II) and Ni(II) complexes from a tridentate NNO Schiff base: Crystal structures, spectral aspects and Hirshfeld surface analysis. (15th January 2019) - Jayendran, Manjari; Sithambaresan, M.; Begum, P.M. Sabura; Kurup, M.R. Prathapachandra
Graphical abstract: The synthesis and structural characterization of a tridentate NNO donor Schiff base ligand and its cadmium and nickel complexes are discussed. An attempt to quantify the various intermolecular forces is made through Hirshfeld surface analysis. The photoluminescence properties of the ligand and its complexes are discussed in detail. Abstract: A tridentate NNO donor Schiff base, 2, 4-dichlorido-6-((3-(dimethylamino)propylimino)methyl)phenol (HL) and its three complexes [CdL2 ]·H2 O (1 ), [NiL2 ] (2 ) and [NiLL′(DMF)] (3 ) (HL′ = 3.5-dichlorosalicylaldehyde) were synthesized and physicochemically characterized by means of elemental analysis, molar conductivity measurements, FT-IR, UV–Vis and NMR spectral studies. The molecular structures of all three complexes were confirmed by X-ray crystallography. In all three complexes, the metal ions are in distorted octahedral environments. [CdL2 ]·H2 O (1 ) crystallized in a triclinic space group, whereas both [NiL2 ] (2 ) and [NiLL′(DMF)] (3 ) crystallized in the monoclinic crystal system. The crystal structures of the complexes exhibit different types of intermolecular interactions, which have been supported by Hirshfeld surface analysis and associated fingerprint plots. The luminescent properties of the Schiff base and the three complexes were studied, and the nature of the emission was found to be quenching.